Physical Literacy in Elementary School Physical Education: A Systematic Review of Teaching Models and Student Development - Herli Pardilla; Syamsuyurnita Syamsuyurnita; Andi Nur Abady; Muhammad Isnandar; Willette Nance; Velorine Gordichev (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: Physical literacy (PL) has been positioned internationally as a foundational goal of quality physical education (PE), yet its translation into concrete pedagogical models for elementary school settings remains fragmented across national curricula and research traditions. This systematic review aimed to synthesise evidence on (a) the dominant teaching models used to cultivate PL in elementary school PE, (b) their documented effects on students' physical, cognitive, affective, and social development, (c) how PL is conceptualised and assessed, and (d) the barriers, enablers, and methodological gaps that shape the field. Materials and methods: Following the PRISMA 2020 framework, a systematic search was conducted in Scopus, Web of Science, and PubMed for peer-reviewed studies published between January 2015 and July 2026. Boolean strings combined terms for physical literacy, teaching/pedagogical models, and elementary/primary school physical education. After de-duplication and two-stage screening (title/abstract and full text) against pre-specified eligibility criteria, 46 studies were retained for narrative and thematic synthesis; methodological quality was appraised using design-appropriate checklists (Mixed Methods Appraisal Tool for empirical studies and AMSTAR-2 for reviews). Results: Included studies originated predominantly from Canada, Indonesia, Spain, the United States, Slovakia, South Korea, and Australia, using quasi-experimental, mixed-methods, qualitative, and instrument-development designs. Five clusters of teaching models emerged: (1) physical-literacy-enriched pedagogy grounded in Whitehead's holistic framework, (2) game-centred approaches (Teaching Games for Understanding and Sport Education, alone or combined), (3) movement-integrated/cross-curricular instruction, (4) game- and play-based models rooted in local or traditional games, and (5) collaborative/team-teaching configurations involving generalist and specialist teachers. Across models, physical competence and motor skill outcomes were the most consistently improved, whereas cognitive and social-affective domains were addressed less systematically and yielded more heterogeneous effects. PL assessment remained fragmented, dominated by physical-domain instruments, with limited validated tools for the cognitive and affective domains in children under 12 years. Key barriers included limited teacher training, ambiguous curricular operationalisation, assessment burden, and short intervention durations; enablers included professional development, co-teaching, autonomy-supportive and play-based pedagogy, and administrative support. Conclusions: The evidence base supports physical-literacy-oriented pedagogy as a promising, holistic reform in elementary PE, but the field is constrained by conceptual heterogeneity, short-term quasi-experimental designs, and uneven attention to non-physical developmental domains. Sustained, theory-driven, and cross-culturally validated research is needed to consolidate PL as an evidence-based pedagogical standard in global primary education.